Strategies to minimize intraoperative blood loss during major surgery - Shah, A; Palmer, AJR; Klein, AA (Wiley, 2020)
Background Reducing operative blood loss improves patient outcomes and reduces healthcare costs. The aim of this article was to review current surgical, anaesthetic and haemostatic intraoperative blood conservation strategies.